Managing Community Participation in Rural Transport Infrastructure Development in Southeastern Provinces, Vietnam - PHIN, Trinh Thi; QUYET, Nguyen Xuan; HAI, Dinh Tuan (Journal of the Eastern Asia Society for Transportation Studies, 2024)
From 2010 to 2019, Vietnam through the rural transport development program has built and repaired 345,897 km, 31,364 bridges, 125,639 sewers to increase the ratio of rural roads from 37.90% in 2010 to 68.69% in 2019. However, the mechanism of policies and management models still has many shortcomings, lack of democracy and explicit, limited management, management capacity has not met the requirements, discovering many mistakes, causing doubts in the community, leading to a complaint. By using directions quantitative and quantitative researches, the article assesses the current situation and analysis of four groups of factors affecting community participation management for developing rural infrastructure. The paper thereby proposes practical solutions and models for community participation management in developing rural transport infrastructure in the southeast provinces of Vietnam.